Influence of male courtship intensity and male–male competition on paternity distribution in Hermann's tortoise, Testudo hermanni hermanni (Chelonia: Testudinidae). (21st February 2014) - Cutuli, Giulia; Cannicci, Stefano; Vannini, Marco; Fratini, Sara
<x xml:space="preserve">Abstract</x> Honest‐advertisement models of sexual selection suggest that condition‐dependent male secondary sexual characters could function as reliable signals of male quality, enabling females to discriminate among potential partners, both in the pre‐ and post‐copulatory phases. In this context, many studies have revealed the importance of promiscuous mating systems and female sperm storage in determining the occurrence of such a model of sexual selection. By contrast, few studies have investigated the presence and extent of post‐copulatory female choice in chelonian species. The present study aimed to investigate the effect of male size, male–male competition, and courtship intensity on paternity distribution in Testudo hermanni hermanni, combining behavioural and genetic data. We created experimental groups composed of two males of different sizes and three or four randomly selected females. Observations conducted during social interactions between males revealed that a hierarchy, unrelated to male size, was soon established: Alpha males were more aggressive towards competitors and courted females more intensively. Alpha males also achieved a higher mounting success than Beta males. Paternity analysis performed on hatchlings produced from experimental females revealed that male reproductive success was not correlated with male–female size ratio. Finally, despite the higher mounting success of Alpha males, paternity analysis revealed that male reproductive success did not differ between Alpha and Beta males. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 111, 656–667.